2015
DOI: 10.1097/qad.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Time above 1500 copies

Abstract: Objective We examined HIV transmission potential of patients in care by analyzing the amount of person-time spent above a viral load threshold that increases risk for transmission. Design Observational cohort and supplemental data. Methods The cohort included HIV patients who received care at six HIV clinics in the United States, from 1 April 2009 to 31 March 2013, and had two or more viral load tests during this interval. Person-time (in days) above a viral load of 1500 copies/ml out of the total observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 15 publications
1
35
1
Order By: Relevance
“…The proportion of person-time in care that was spent with HIV RNA >1500 copies/mL (15%) in our study was less than that found in a prior study to which our cohort contributed data (23%) (26) and to a study in the HIV Outpatient Study (24%) (27). This may be explained by differences in the study populations, but also by the fact that our sample was in care during a slightly more recent time period (2010–2015 versus 2009–2012 and 2000–2014, respectively) while norms about ART initiation were changing rapidly.…”
Section: Discussioncontrasting
confidence: 74%
“…The proportion of person-time in care that was spent with HIV RNA >1500 copies/mL (15%) in our study was less than that found in a prior study to which our cohort contributed data (23%) (26) and to a study in the HIV Outpatient Study (24%) (27). This may be explained by differences in the study populations, but also by the fact that our sample was in care during a slightly more recent time period (2010–2015 versus 2009–2012 and 2000–2014, respectively) while norms about ART initiation were changing rapidly.…”
Section: Discussioncontrasting
confidence: 74%
“…Those who did not sustain durable viral suppression also spent an average of 60% of the 2-year time with VL above 200 copies/mL as well as a considerable length of time above 1,500 and 10,000 copies/mL, posing risk for further transmission. 5,15 The dynamic VL trajectories are easily overlooked with the cross-sectional assessment of last VL measure, which revealed 82.9% suppression in the analytic cohort. Clearly, these longitudinal measures of VL dynamics provide more granular data with implications for HIV treatment and prevention.…”
Section: Discussionmentioning
confidence: 97%
“…Using the method developed by Marks et al, 15 we estimated the amount of time (in days) spent above 1,500 copies/mL for each pair of VL results, summed the estimated days above the 1,500 cut-point during consecutive pairs of VL results to yield a single value per person, and then aggregated the amount of person-time above the cut-point across the analytic cohort over the 2-year period. Given evidence suggesting a dose-response relationship between increasing plasma viremia and sexual transmission in serodiscordant couples, 5 we also used a higher plasma level (10,000 copies/mL) to examine HIV transmission risk potential.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations